2017
DOI: 10.4085/1062-6050-50.5.01
|View full text |Cite
|
Sign up to set email alerts
|

Previous Knee Injury and Health-Related Quality of Life in Collegiate Athletes

Abstract: Despite returning to full participation, collegiate athletes who previously sustained severe knee injuries tended to report worse knee-specific function and less ability to complete activities due to physical health. In addition, individuals with a history of severe knee injury tended to report more emotional concerns than athletes with a history of mild or no knee injury. Region-specific PROMs may be more sensitive in detecting deficits than generic PROMs after return to full participation. Researchers should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…In the present study, 45% of participants needed more than 4 weeks to recover after their knee injuries and they were unable to return to their level of activity prior to the injury, others needed less time to recover. In comparison with other studies that reported decrease in the ability of some patients to carry out their previous level of physical activity even after they were cleared by their healthcare providers [49,50]. Knee injury is a wellknown risk factor for the development of early knee osteoarthritis [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, 45% of participants needed more than 4 weeks to recover after their knee injuries and they were unable to return to their level of activity prior to the injury, others needed less time to recover. In comparison with other studies that reported decrease in the ability of some patients to carry out their previous level of physical activity even after they were cleared by their healthcare providers [49,50]. Knee injury is a wellknown risk factor for the development of early knee osteoarthritis [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…Evaluating the domains of disablement and dimensions of HRQOL that are affected after injury is essential to providing comprehensive athletic health care and helps to ensure that attention to the health condition extends beyond impairments. Authors investigating how musculoskeletal [20][21][22][23][24][25][26][27][28][29] and head [30][31][32] injuries affected patients found that deficits were reported across a broad spectrum of health categories and beyond impairments and physical function. These results highlight the need for PRO instruments to capture the whole-person perspective of health in order to better guide patient care decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This multidimensional health construct is evaluated by the patient and encompasses a variety of health areas, such as psychological, physical, and social health. [15][16][17][18][19] Additionally, HRQOL can be influenced by events, such as injury [20][21][22][23][24][25][26][27][28][29][30][31][32] ; thus, it should be a focus of patient care, especially when evaluating and managing the condition. Recently, the National Athletic Trainers' Association adopted the World Health Organization's International Classification of Functioning, Disability, and Health (ICF) disablement model for the profession.…”
mentioning
confidence: 99%
“…There is a paucity of literature on using the SF-12 in a physically active population with musculoskeletal injury. 24 Statistical Analysis. Descriptive statistics, including the median and interquartile range, were calculated for all variables.…”
Section: Instrumentationmentioning
confidence: 99%